ANALISIS MAJAS PADA CERITA PENDEK â€œKEMARAUâ€ KARYA ANDREA HIRATA - Yesa Ika Trisnawati; Ika Mustika; Enung Nurhayati (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
This study aims to analyze the figure of speech or language style contained in the short story "Kemarau" by Andrea Hirata. The method used in this research is descriptive qualitative method. This research was carried out by reading the short story carefully and thoroughly, then analyzing and marking each sentence or word included in the figure of speech, then from the data that had been reviewed or analyzed the writer found various kinds of figure of speech in the short story "Kemarau", including the personification figure of speech, hyperbole figure, simile figure and cynicism figure. The number of personified figures is 11, the hyperbolic figure is 17, the simile figure is 2 and the cynic figure is 7.